Identification of Genes Encoding the Production of Bacteriocin from Lactiplantibacillus Plantarum and its Activity Against Some Pathogenic Bacteria in Kirkuk City - Wasan Fahem; Salah Zain Alabdeen; Asal Tawfeeq (Kirkuk Journal of Science)
Our previous research results showed that through microscopic and biochemical detection of single pure colonies,we obtained 45 positive samples of lactic acid bacteria isolated from cow milk in Kirkuk City In addition 40 isolates of pathogenic bacteria (10 isolates each of Staphylococcus aureus, Staphylococcus epidermidis,Pseudomonas aeruginosa and Escherichia coli) were obtained from Kirkuk City Hospitals during the period from December to February 2021.The results were displayed subsequent to their comparison with the non-inoculated culture medium. The same extraction procedures were conducted on this medium to assess the inhibitory effects of both the initial(supernatant)and final(deposits) extraction steps against two isolates of each gram-positive and gram-negative pathogenic bacteria. Consequently, we conducted molecular studies to evaluate the effectiveness of Lactobacillus isolates against these pathogenic strains. Geneious Prime 2021version 2.2 software was utilized to identify genes associated with bacteriocin production, specifically PlnK, PlnN, PlnEF, and PlW.